Relationship between articular eminence inclination and alterations of the mandibular condyle: a CBCT study - Saione Cruz SA; Saulo Leonardo Sousa MELO; Daniela Pita de MELO; Deborah Queiroz FREITAS; Paulo Sérgio Flores CAMPOS (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study aimed at verifying the correlation among angulation of the articular eminence (AE), shape of the condyle and its degenerative bone diseases (DBDs), according to age and sex, through Cone Beam Computed Tomography (CBCT). Five hundred and twenty-eight temporomandibular joints (TMJ) were evaluated. The condyles were classified as: flat, convex, angled and rounded, and the AE angulation was measured. The DBDs evaluated were osteophytes, flattening, erosion, subcortical cysts and spinal sclerosis. There was no difference in the mean angulations in relation to age group (p>0.05). In age groups of 60-69 years (p=0.003) and 70 years or over (p=0.021), the angulation was higher in males. There was an association between DBD and sex (p=0.047), in that the prevalence was higher in females. Differences in AE angles were not observed in condyles with one or no DBDs (p>0.05). However, the presence of two or more DBDs led to a decrease in the angle (p<0.05). Angled condyles showed higher AE angulations than the flat and convex types (p<0.01). In conclusion, the AE inclination is influenced by DBD and condyle shape; an association of two or more bone diseases in the condyle, or its flat or convex anatomy, results in a decrease in the angulation.